Metods of promoting Islamic values among youth and their impact on spiritual development - Kabylbayeva, N.; Begalinova, К.; Mohd Nor, Mohd Roslan (Eurasian Journal of Religious Studies, 2026)
This article provides a scientific analysis of the ways Islamic values are spreading among today's youth and their influence on the development of their spiritual worldview. In the context of information technology and globalization, youth value orientations are changing, and the importance of fundamental spiritual values is growing. In this context, Islamic values – morality, faith, dignity, and tolerance - are viewed as key factors in shaping the personal qualities of young people and regulating their social behavior. The study analyzes the main channels for promoting an Islamic worldview among young people, primarily the family institution and the education system (schools and universities), religious organizations, and the digital information space. The family is the primary environment for spiritual education, while schools and educational institutions are viewed as institutional settings that enhance young people's religious literacy and foster critical thinking. The role of social media and the digital space in the dissemination of Islam is also analyzed. Based on scientific research by Russian and international scholars, this article substantiates the positive influence of Islamic values on the worldview, moral stability, social responsibility, and spiritual development of young people. The study's findings highlight the need for effective dissemination of Islamic values through the media that have emerged as a result of globalization, in accordance with the principles of a sovereign state.Keywords: Islamic values, education, Kazakhstani youth, family, spirituality